Pengaruh Loyalitas Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Idexpress Logistik Indonesia (Pagedangan) - Nurul Faiziah; Aden Prawiro Sudarso (Jurnal Publikasi Ilmu Manajemen, 2023)
The purpose of this research is to determine the influence of loyalty and work discipline on employee performance at PT IDExpress Logistics Indonesia, Pagedangan branch, South Tangerang, partially and simultaneously. The research approach used in this research is the Quantitative Method. The sampling technique used in this research used saturated sampling with a sample size of 51 people. The data collection technique in this research uses a questionnaire distributed to employees of PT IDExpress Logistics Indonesia. Data analysis techniques Data using Descriptive Analysis, Validity Test, Reliability, Simple, Multiple Regression Analysis, Classical Assumption Test, t Test (Partial), F Test (Simultaneous), Correlation Coefficient and Determination. Data processing in the research used SPSS 26. Based on the research results, the results of the multiple linear regression test showed that the regression coefficient value was Y = 7,104+ 1.395X1 + 0.702X2. The results of the simultaneous test produced a significance value of 0.001 <0.05, which means that Loyalty and Work Discipline influence employee performance. Furthermore, the results of the coefficient of determination show a figure of 0.791, so 79.1% of work loyalty (X1) and work discipline (X2) influence employee performance (Y) at PT IDExpress Logistics Indonesia, while the remaining 20.9% is influenced by variables. another. Thus it can be concluded that the first hypothesis (Ha1), second hypothesis (Ha2), and third hypothesis (Ha3) can be accepted.